Trans-Substantial Motion (Al-Harakah Al-Jawhariyyah) Toward a Holistic Evolutionary Theory Traditional Contribution to Islamic Philosophy of Science - Zubaidah Yusuf (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2015)
The modern evolution theory which starts its growth in popu- larity from the phenomenal Darwin’s the Origin of Species published in 1859. Inspired by Malthus’s essay on human populations competing for limited resource, he found a clue for a theory to interpret the voluminous data he had collected on the H.M.S Beagle voyage wherein he served as a naturalist for five years. Darwin had noted the gradual changes in successive generations to the “natural selection” of heritable characteristics that contribute to survival. This paper elaborated the thesis of new species which comes into existence by variation and selection over a long period of time.